Optimal environmental drivers of high-mountains forest: Polylepis tarapacana cover evaluation in their southernmost distribution range of the Andes - López, Victoria Lien (2022)
The Andes Mountains are considered a global biodiversity hotspot, where Polylepis forests are one of the most threatened forests in the area. We evaluate the P. tarapacana forest’s distribution and cover and relate this pattern with topographic, climatic and geographic environmental factors at the landscape level. Along 93 plots, forest structure data was conducted according to their homogeneity, accessibility, and size (patches up to > 1 ha each). Hexagon binning processes were used to estimate the forest cover, as the proportion of hexagon area covered by forests, and one-way ANOVAs were conducted to evaluate its variation according to the environmental factors. Our results show that P. tarapacana forests are widely distributed, occupying a forest area of 8519.8 ha among 2462 forest patches and an average of 6.7% of forest cover (1296 hexagons - 129600 ha). According to the findings, the entire forest distribution encompasses a wide range of environmental conditions. We identify that the slopes and elevations were the main environmental drivers that shaped P. tarapacana distribution and cover. Variations in forest area and cover indicate a strong preference for north and east-facing slopes (18 and 24◦) and intermediate elevations (4400 - 4500 m a.s.l), with a life zone of Tropical subalpine dry scrub accounting for 62.1%. Our research shows that remote sensing mapping and geographic information systems are effective methods for identifying habitat variables linked to threatened forest cover and evidence of forest vulnerability in the face of continuous global change.